Ascorbic acid concentration of native Andean potato varieties as affected by environment, cooking and storage - Burgos, G.; Auqui, S.; Amoros, W.; Salas, E.; Bonierbale, Merideth W. (Elsevier, 2009)
The ascorbic acid (AA) concentration of tubers was determined in 25 Andean potato varieties (Solanum tuberosum L.) grown in three environments, and the effect of cooking and storage time in subsets of samples was evaluated. Significant variation due to genotype, environment and genotype × environment (G × E) interaction was found. AA concentration in freshly harvested raw, peeled tubers ranged from 22.2 to 121.4 mg/100 g on a dry weight basis (DW) and from 6.5 to 36.9 mg/100 g on a fresh weight basis (FW) with the accession 704393 showing the highest levels of AA in all three locations. Differences in AA concentration were found among cooking methods and storage times; and significant non-crossover interactions with genotype were observed for both of these parameters. It was found that AA concentration of boiled tubers of the six varieties evaluated was higher than in oven and microwaved tubers and that AA concentration of tubers of the 23 varieties evaluated decreased with storage time. The variety 704393 retained 54 and 34% of its original AA concentration after boiling and storage during 26 weeks under farmer conditions. One hundred grams of fresh harvested boiled potatoes of this variety (704393) could provide adults with 17–20% of the recommended daily allowance (RDA) of AA.